Barthes's Body of Knowledge - Gregory L. Ulmer (Studies in 20th & 21st Century Literature, 1981)
Roland Barthes invites a reading of his own texts in terms of the same methodologies he employs in his criticism. The «Biographeme»—those few details, preferences, inflections—which Barthes identified in his favorite authors, may be sought in Barthes as well. Barthes's biographeme, for me, consists of a glutinous effect associated with the organs of the mouth and throat as presented in several images, some of which belong to his tutor texts (Poe and Réquichot). An analysis of this biographeme reveals Barthes's strategy for disseminating the subject of knowledge—the author's fantasmatic body—through the signifiers of writing, fusing the heterogeneous singularities of the knower and the object of study. The metaphorical discourse that results opposes normal academic preoccupations in favor of knowledge of/as desire. Knowledge itself in Barthes becomes a second order signifier caught up in a catachretic process for naming the real. Barthes's procedure for exploring the real affectively, in terms of the body as it is defined in psychoanalysis, imposes on the reader a similar obligation to bring his or her own body into play in the learning experience. Barthes offers a model for a new genre of academic writing, combining science with autobiography, that has important implications for teaching and research in the humanities and social sciences.
Keywords: Roland Barthes; Biographeme; Poe; Réquichot; fantasmatic body; body; catachretic